Synthesis of New Polymers Derived from Poly (Vinyl Chloride) and Study Their Optical Properties - Al-Daeif, Yasmeen; Yousif, Emad; Nabi, Mohammed Abdul (Al-Nahrain Journal of Science, 2012)
Poly (vinyl chloride) (PVC) react with different amines in THF to form new polymers (PVC-L), which been characterize by spectroscopic methods. The structures of these complexes have been characterized by IR and Uv-Vis. Spectrophotometry. The optical properties of PVC in the region from (200-600 nm) were studied by preparing the composites PVC-L. The optical data analyzed and interpreted in term of the theory of phonon assisted direct electronic transition; it is observed that the energy is affected by doping type polymers used.